Mobile Phone Based Indoor Mapping - C. Strecha; M. Rehak; D. Cucci (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2024)
We presented a mobile phone scanning solution that offers a workflow for scanning not only small spaces, where drift can be neglected, but also larger spaces where it becomes a major accuracy issue. The LiDAR and image data is combined to build 3D representations of indoor spaces. The paper does focus on the drift compensation for larger scans on the mobile phone by using AutoTags detections. We show that those can also be used to combine scans from multiple independent scans.